What are the support experiences and needs of patients who have received bariatric surgery?. (2nd November 2015) - Sharman, Melanie; Hensher, Martin; Wilkinson, Stephen; Williams, Danielle; Palmer, Andrew; Venn, Alison; Ezzy, Douglas
Abstract: Objective: To explore the support needs and experiences of patients who had received publicly or privately funded bariatric surgery and the importance of this support in mediating outcomes of surgery. Methods: Seven semi‐structured focus groups were conducted. A broad interview schedule guided the discussions which were audio‐recorded and transcribed verbatim. Data were analysed thematically. Results: Twenty‐six women and 15 men with a mean age of 54 years (range 24–72) participated in the study. Participants described support needs from health professionals, significant others (family and friends), peers (bariatric surgery recipients) and the general community. Peer, dietetic and psychological support were identified as important factors influencing the outcomes (e.g. weight reduction or health improvement) or experience of bariatric surgery but were identified as infrequently received or inadequately provided. Psychological support was proposed as one of the most significant but commonly overlooked components of care. Support needs appeared higher in the first year post‐surgery, when subsequent related or unrelated surgeries were required and following significant life change such as worsening health. For some participants, deficits in support appeared to negatively influence the experience or outcomes of surgery. Conclusion: Providers of bariatric surgery should discuss support needs and accessibility regularly with patients especially in the first year post‐surgery and following significant change in a patient's life (e.g. declined health or childbirth). Nutrition, psychological and peer support (e.g. through support groups) may be especially important for some patients.